Optimization of Glucose as Source of Bioethanol from Reed (Imperatacylindrica) Using Cellulase Enzyme at Various pH and Substrate Particle Size - Eti Indarti; Yusya Abubakar; Normalina Arpi; . Satriana; Yuza Arfiansyah (Syiah Kuala University, 2012)
Due to increasing demand of petroleum and limited source of fossil fuel, it isneeded to explore and find source of a renewable energy. The biomass from agricultural residues, forest and farm waste has been known as a great source of energy and can be converted into biogas, bioethanol, biodiesel, etc. Reed which is abundant in Indonesia is one of potential sources of lignocellulose biomass that can be utilized as (Imperata cylindrica) a source of renewable energy such as bioethanol. The aim of this study was to optimize yield of glucose from reed using cellulose enzyme. Factors used in this research werepH and substrate particle size. Reed particle sizes were 80 and 100 mesh and pH of the solution were 4.2, 4.8 and 5.5. The results showedthat dried reedwith100 meshes in particle size which hydrolysed in enzyme solution with pH 5.5 at 37oC for 72 hours, producedthe highest yield of glucose in the amount of 80.2 mg/ml (8.02 %). When the incubation time was extended, glucose yield increased to 121.8 mg/ml (12.1%) at 96 hours and then decreased as the incubation time was extended further